Revealed comparative advantage (RCA), export diversification, and economic performance in selected Asian countries - Faiznur, Binti Yusuf. (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study aims to investigate the Revealed Comparative Advantage (RCA) for the Asian five countries which are Malaysia, Indonesia, Singapore, China and Japan and their export diversification which can help to generate a high economics performance. The RCA index is applied in this study to generate the standard deviation of RCA so that it can be used to analyze the export diversification from the year 1976 until 2010. The finding indicates that Japan is the most diversify exports country followed by Singapore, Malaysia, China and Indonesia. For the economic performance, it shows that these selected Asian have achieve a high economic performance since an export is a major component in computing the economic income. Although the country export is competitive, it does not mean that the export is diversified.